Asuhan Keperawatan Jiwa pada Tn. S dengan Masalah Utama Risiko Perilaku Kekerasan Akibat Skizofrenia Paranoid di Ruang Gatotkaca RSJD dr. Amino Gondohutomo Provinsi Jawa Tengah - Syifa Auliatul Khasanah; Titi Sri Suyanti; Tati Karyawati (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Metal disorders are syndromes caused by various typical behaviors related to the symptoms of suffers in which one or more important functions of humans include psychological functions, biological behavior that can cause disturbances in society. The purpose of this paper is to find out nd provide psychiatric nursing care to Mr. S with the main problem of the risk of violent behavior due to paranoid schizophrenia in the Gatotkaca ward of the dr. Amino Gondohutomo Mental Hospital, Central Java Province in accordance with nursing standards. The method used is a descriptive method in the form of interviews, observations, documentation studies and literature studies. From the case review, it was found that the patient’s main complaint said “at home I get angry, shout and damage things, I wander around carrying a knife, ma’am”. There are 4 nursing problems, namely violent behavior, risk of violent behavior, low self-esteem and self-care deficit. Interventions are arranged based on TUM and TUK as well as on the client’s condition and can be implemented.